ANALISIS PENGARUH PERTUMBUHAN EKONOMI, INFLASI, EKSPOR DAN JUMLAH UANG BEREDAR TERHADAP RISIKO KREDIT DI WILAYAH ASIA TENGGARA (ASEAN) (STUDI PADA NEGARA THAILAND, FILIPINA, MALAYSIA DAN INDONESIA PERIODE 1998-2014) - Wulandari, Fitria (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aimed to examine the effect of economic growth, inflation, exports and the money supply on credit risk in the region of Southeast Asia (ASEAN). The author uses nonperforming loans as the dependent variable and include variables of economic growth, inflation, exports and money supply as an independent variable. The author uses quantitative research methods and using panel data analysis that the merger between the data time series and cross section data.The results showed that the variable economics growth (GDP) and export significant and negative influential on credit risk in ASEAN, while the inflation Â influence significantly and positive on credit risk in ASEAN and variable money supply does not significantly influence the credit risk in ASEANKeywords: Credit Risk, Non Performing Loan, GDP, Inflation, Export, Money Supply